Combined linkage and association mapping reveal QTL for host plant resistance to common rust (Puccinia sorghi) in tropical maize - Zheng, H.; Chen, J.; Mu, C.; Makumbi, Dan; Xu, Y.; Mahuku, George S. (Springer, 2018)
Background Common rust, caused by Puccinia sorghi, is an important foliar disease of maize that has been associated with up to 50% grain yield loss. Development of resistant maize germplasm is the ideal strategy to combat P. sorghi.